Effectiveness of PRP (Platelet Rich Plasma) To Increased BMD (Bone Mineral Density) At Maxilla Dental Implant Placement with 3-Dimensional Radiographic Examination (CBCT) - Dianty Saptaswari; Yoifah Rizka Wedarti; Hansen Kurniawan (Denta Journal Kedokteran Gigi, 2017)
Background: Dental implant is a device that is surgically implanted into the soft tissue or into the jaw bone. dental implants have become the treatment of choice for replacing missing teeth. Platelet rich plasma and platelet concentration derived from autologous blood containing autologous growth factors in which the platelet rich plasma can improve wound healing and increase the regeneration of bone. today cone beam computed tomography (CBCT) has been available for 3D visualization of craniofacial section. CBCT 3 D is able to provide information on the general bone mineral density. Purpose: The purpose of this studywas to determine thebone mineral density by three-dimensional radiographic picture after dental implant placementbyan additional plateletrich plasma. Material and Method: This study was divided into 2 groups. The first placement of a dental implant with platelet rich plasma and the second placement of a dental implant without platelet rich plasma. Results: there are significant differences in dental implant placement with platelet rich plasma and placement of dental implants without platelet rich plasma. In the test results obtained Independent T test (p = 0.02). Conclusion: There was an increase bone mineral density in dental implant placement with platelet rich plasma were performed using three-dimensional radiographic examination (CBCT).